Taylor Swift is life : a superfan$1 (Bs guide to all things we love about Taylor Swift /s - Perricone, Kathleen (USA : Quarto, 2024)
A full biography capturing her early inspiration and first performances through her through her sensational 2023-2024 Eras Tour A full discography of Taylor$1 (Bs music, including the significance of each album personally and professionally, the meaning behind every Track 5, and all the hidden Easter eggs and symbolism behind the songs.s
Music Pop Culture.
Text in English
Keywords: Biography Book